Metal–organic framework nanoparticles for arsenic trioxide drug delivery. Issue 40 (24th September 2018) - Ettlinger, Romy; Sönksen, Marthe; Graf, Monika; Moreno, Natalia; Denysenko, Dmytro; Volkmer, Dirk; Kerl, Kornelius; Bunzen, Hana
Abstract : As2 O3 was introduced as an anion into MOF nanoparticles via a postsynthetic ligand exchange; material cytotoxicity was investigated in vitro . Abstract : Arsenic trioxide is a double-edged sword: On the one hand it is known as a poison, on the other hand it is used as an anticancer drug. Though effective in the treatment of leukaemia, arsenic trioxide has not been able to be introduced into the treatment of solid tumour entities yet due to its dose-limiting toxicity. However, different in vitro and in vivo studies revealed arsenic trioxide to be a potent agent against different solid tumour entities, including atypical teratoid rhabdoid tumours (ATRT), a paediatric brain tumour entity with a very poor prognosis. To improve the pharmacokinetics and therapeutic efficacy of arsenic trioxide and to reduce its toxic side effects, we propose to use a metal–organic framework (MOF) as a drug carrier material. Herein we report on using a MOF called MFU-4l (Metal–Organic Framework Ulm University), consisting of Zn(ii ) ions and bis(1 H -1, 2, 3-triazolo[4, 5- b ], [4′, 5′- i ])dibenzo[1, 4]dioxin ligands, to deliver arsenic trioxide in a form of dihydrogen arsenite anions. The H2 AsO3 − anions were introduced to the MOF in a nanoparticle formulation via a postsynthetic side ligand exchange. The prepared material was characterised by IR, TGA, XRPD, SEM-EDX, TEM, DLS, ICP-OES and adsorption analysis. The drug release studies at different pH values were carried out as well as cytotoxicity tests with different ATRT cell lines and non-tumorous-control cell lines. The MOF-based material was shown to be a promising candidate for arsenic trioxide drug delivery.